Conducta obstétrica en embarazo gemelar y trabajo de parto en periodo. - Lemay Tayupanda, Jessica Patricia (2022)
Twin pregnancy is associated to a greater extent with maternal and fetal complications. They are the most likely to reflect more frequently abortions, hyperemesis gravidarum, and other complications present. On the other hand, expulsive labor is identified with being complete cervical dilation and delivery of the fetus. Characterized by the desire to "push" generated by the pressure of the baby's head on the pelvic floor. The present clinical case is of a 28-year-old patient, with a pregnancy of 39 weeks of gestation by Echo, who attends for an emergency oriented in time and space, afebrile, who is admitted due to pain in the hypogastrium that radiates towards the sacral lumbar region… It is very important and necessary to provide prompt and effective care, in addition to safeguarding adequate obstetric behavior to avoid potentially fatal complications in these patients that can cause death.